2021
DOI: 10.1039/d1cp01359a
|View full text |Cite
|
Sign up to set email alerts
|

Three-step Förster resonance energy transfer on an amyloid fibril scaffold

Abstract: The present study provides evidence that the energy transfer chain consisting of the benzothiazole dye Thioflavin T as an input donor, a phosphonium dye TDV and a squaraine dye SQ4...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…FRET systems involve the presence of a significant amount of chromophores able to mainly absorb light radiation, e.g., in the visible region of the spectrum (this is addressed in more detail below). Importantly, these artificial systems would be suitable for generating multi-step mechanism directional energy transfer of the absorbed radiation energy [88]. These chemical environment conditions would allow for reaching photoactive centers separated by distances in the order of nanometers.…”
Section: Photo-induced Energy Transfer Processesmentioning
confidence: 99%
“…FRET systems involve the presence of a significant amount of chromophores able to mainly absorb light radiation, e.g., in the visible region of the spectrum (this is addressed in more detail below). Importantly, these artificial systems would be suitable for generating multi-step mechanism directional energy transfer of the absorbed radiation energy [88]. These chemical environment conditions would allow for reaching photoactive centers separated by distances in the order of nanometers.…”
Section: Photo-induced Energy Transfer Processesmentioning
confidence: 99%
“…It is of interest to investigate if the prepared materials can be employed for applications involving donor–acceptor pairs of dyes. There has been much interest recently in mimicking natural light-harvesting processes by achieving efficient energy transfer from donors to acceptors through the Förster resonance energy transfer (FRET) process. Such an approach can moreover be employed to achieve systems capable of emission of white light.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades the phosphonium-based optical probes attract ever growing interest due to their favorable characteristics, namely, the excellent chemical and photophysical stability, high aqueous solubility, long wavelength absorption and emission, large extinction coefficient, high fluorescence quantum yield, low cytotoxicity, etc [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The above properties render phosphonium dyes highly suitable for the selective staining of mitochondria [3][4][5], antioxidants detection [6,7], probing the structural differences of DNA/RNA grooves [1,2], exploring the tumor multidrug resistance [8], to name only a few.…”
mentioning
confidence: 99%
“…Moreover, the phosphonium conjugates proved to be very effective in monitoring the oxygen variations within mitochondria [10] and measuring the hydrogen peroxide levels [11]. Furthermore, numerous studies have demonstrated that phosphonium fluorescent dyes can be effectively used for optical detection of disease-related protein aggregates, amyloid fibrils [12,13]. In particular, a phosphonium dye TDV was used as a mediator in the amyloid-scaffolded multichromophoric systems for monitoring the amyloid transformation of the N-terminal fragment of apolipoprotein A-I [12] and insulin [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation